The Thematic Representation of Female Composers in Classical Music on Streaming Platforms - Tolare, Jessica Beatriz; Novaes, Fernanda Carolina Pegoraro; Silva, Amanda Mendes (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie, 2024)
Women have been increasingly fighting for their rights and equality in Society. Historically, in the 18th century, women’s musical education was considered a distraction and participation in family events, but professional engagement was not deemed acceptable. Given this context, questions arose about the existence of female classical music composers and whether their works are present on current music streaming platforms. Based on this, the study aimed to investigate how these composers are thematically represented on these platforms. Methodologically, the study is qualitative and exploratory, employing case study methods. The search terms used were “woman” and “classical music” along with the composers' names. The criterion for selecting composers was that they belonged to the 18th, 19th, and 20th centuries, as many male composers achieved enduring success during this period. The selected composers were Maria Anna Mozart, Fanny Mendelssohn, Clara Schumann, Chiquinha Gonzaga, and Alma Mahler-Werfel. The chosen platforms were Spotify, Amazon Music, Deezer, and Apple Music. The research demonstrated a scarcity of historical records about the analyzed composers’ lives. They were often compelled to abandon music due to family obligations, which contributed to the limited availability of their music on the platform.